Long, fine aramid monofilament, manufacturing method thereof, and composite material and sheet including long, fine aramid monofilament

A method for producing long, fine, and highly crystalline aramid fibers using a swelling and mechanical defibration process addresses the limitations of existing technologies, resulting in fibers with improved mechanical properties and industrial applicability.

JP2025008135APending Publication Date: 2025-01-20TOKUSHU TOKAI PAPER
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023110047
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing methods for producing aramid fibers result in relatively short fibers with low crystallinity.

Method used

A method involving a swelling step with an aprotic solvent, followed by mechanical defibration, to produce long fine aramid single fibers with a maximum diameter of less than 2000 nm and a crystallinity of 60% or more, using meta-aramid as the preferred aramid type.

Benefits of technology

The method produces aramid fibers that are extremely thin, long, and highly crystalline, with improved industrial productivity and enhanced mechanical properties when combined with resins.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008135000003
    Figure 2025008135000003
  • Figure 2025008135000004
    Figure 2025008135000004
  • Figure 2025008135000005
    Figure 2025008135000005
Patent Text Reader

Abstract

To provide an aramid monofilament which is very thin, long, and high in crystallinity.SOLUTION: A long, fine aramid monofilament has a maximum fiber diameter of less than 2000 nm, a minimum fiber length of more than 10 μm, and crystallinity x of 60% or more, the crystallinity being determined by an equation: x=(1-ΔQx / ΔQ0)×100(%) (in the equation, ΔQx is a variation of heat capacity of the long, fine aramid monofilament before and after glass transition point, and Q0 is a variation of heat capacity of amorphous aramid before and after glass transition point).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to very fine and long aramid monofilaments and their production and use. [Background technology]

[0002] Aromatic polyamides (aramids) include para-aromatic polyamides such as polyparaphenylene terephthalamide, and meta-aromatic polyamides such as polymetaphenylene isophthalamide, both of which are in practical use as fibers.

[0003] Furthermore, very thin (fine) fibers made of aromatic polyamides have also been produced. For example, Patent Document 1 describes the production of aramid nanofibers with an average fiber diameter of 20 nm by discharging a solution of aramid in a strong base, dimethyl sulfoxide, into water and spinning the resulting solution (see Patent Document 1, paragraphs

[0051] to

[0053] ). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2023-2089 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the aramid nanofibers obtained by the method described in Patent Document 1 are relatively short and have low crystallinity.

[0006] An object of the present invention is to provide an aramid single fiber which is very thin, long and has a high degree of crystallinity. [Means for solving the problem]

[0007] The first aspect of the present invention is The maximum fiber diameter is less than 2000 nm, A long fine aramid single fiber having a minimum fiber length of more than 10 μm, The following formula x = (1-ΔQx / ΔQ0) × 100 (%) (In the ceremony ΔQx is the change in heat capacity of the long fine aramid single fiber before and after the glass transition point, The crystallinity x determined by the formula (ΔQ0 is the change in heat capacity before and after the glass transition point of amorphous aramid) is 60% or more.

[0008] The long and fine aramid single fibers preferably have an average fiber diameter of less than 1000 nm.

[0009] The long and fine aramid single fibers preferably have an average aspect ratio of 100 or more.

[0010] The long fine aramid single fibers preferably have a glass transition point of more than 300°C.

[0011] The aramid constituting the long fine aramid single fibers is preferably meta-aramid.

[0012] A second aspect of the present invention is A swelling step of bringing raw material aramid fibers having a soluble content in dimethyl sulfoxide of 10% by mass or more into contact with a swelling liquid containing an aprotic solvent to cause the fibers to swell; A mechanical defibration step of finely pulverizing the raw aramid fibers by mechanical defibration; and A separation step of separating long fine aramid single fibers having a fiber diameter of less than 2000 nm and a fiber length of more than 10 μm from the finely divided raw aramid fibers. The method for producing the long fine aramid single fibers includes the steps of:

[0013] Preferably, the aprotic solvent is dimethylsulfoxide and / or dimethylacetamide.

[0014] The glass transition point of the long fine aramid single fibers is preferably higher than the glass transition point of the raw material aramid fibers by 30° C. or more.

[0015] A third aspect of the present invention is a composite material comprising the above-mentioned long fine aramid monofilaments and a matrix resin.

[0016] It is preferable that the long fine aramid fibers are dispersed in the matrix resin.

[0017] The matrix resin is preferably an epoxy resin.

[0018] A fourth aspect of the present invention is a sheet comprising the above-mentioned long fine aramid single fibers. Effect of the Invention

[0019] The long fine aramid monofilaments of the present invention are very fine, long, and highly crystalline.

[0020] The method for producing long and fine aramid single fibers of the present invention can produce aramid fibers which are very thin, long, and have a high degree of crystallinity. The method for producing long and fine aramid single fibers of the present invention has high productivity and is advantageous for industrial production of long and fine aramid single fibers.

[0021] The composite material or sheet of the present invention can exhibit properties derived from the long, fine aramid monofilaments contained therein. [Brief description of the drawings]

[0022] [Figure 1] Electron microscope photograph of the long and fine aramid single fiber obtained in Example 1 [Diagram 2] Electron microscope photograph of the long and fine aramid single fiber obtained in Example 1 [Diagram 3] Electron microscope photograph of the long and fine aramid single fiber obtained in Example 1 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] As a result of extensive investigations, the present inventors have found that it is possible to provide an aramid single fiber which is very thin, long and has a high degree of crystallinity by a given production method.

[0024] As described in Patent Document 1

[0036] , it was thought that mechanical shearing force only partially produces a fibril structure having a nano-order fiber diameter, and that it is not possible to produce aramid single fibers having a nano-order fiber diameter. However, the present inventors have found that it is possible to produce aramid single fibers having a nano-order fiber diameter by using mechanical shearing force, and that it is possible to impart a high degree of crystallinity to the aramid single fibers thus obtained.

[0025] Hereinafter, the long fine aramid single fibers, the method for producing the long fine aramid single fibers, and the composite material or sheet containing the long fine aramid single fibers of the present invention will be described.

[0026] [Aramid] In the present invention, "aramid" refers to an aromatic polyamide. In the present invention, "aromatic polyamide" refers to a linear polymer compound in which, in terms of chemical structure, 60 mol % or more, preferably 70 mol % or more, more preferably 80 mol % or more, and even more preferably 90 mol % or more of amide bonds are directly bonded to aromatic rings.

[0027] Aramids are classified into para-aramids, meta-aramids and copolymers thereof according to the substitution position of the amide group on the benzene ring. Examples of para-aramids include polyparaphenylene terephthalamide and its copolymers, poly(paraphenylene)-copoly(3,4'-diphenyl ether) terephthalamide (poly(paraphenylene)-copoly(3,4'-diphenyl ether) terephthalamide), etc. Examples of meta-aramids include polymetaphenylene isophthalamide and its copolymers. These aramids are industrially produced, for example, by conventionally known interfacial polymerization methods, solution polymerization methods, etc., and are available as commercial products, but are not limited thereto. In the present invention, meta-aramids are preferably selected. Meta-aramids have the following characteristics: they are soluble in general-purpose amide solvents, can be wet-molded using a polymer solution as a starting material, have excellent heat fusion properties, and have good heat resistance and flame retardancy. Among meta-aramids, polymetaphenylene isophthalamide is preferably used since it has good moldability, heat adhesion, flame retardancy, heat resistance, and other properties.

[0028] [Long fine aramid single fiber] The long fine aramid monofilament of the present invention is a monofilament. In the present invention, the term "monofilament" means a fiber without branches, and does not mean a fiber with branches such as a fibrillated fiber.

[0029] The long and fine aramid single fibers of the present invention are very thin (i.e., fine) fibers having a maximum fiber diameter of less than 2000 nm. The maximum fiber diameter of the long and fine aramid single fibers of the present invention is preferably less than 1900 nm, more preferably less than 1800 nm, and even more preferably less than 1700 nm. The maximum fiber diameter of the long and fine aramid single fibers of the present invention may be 1000 nm or more.

[0030] The long fine aramid single fiber of the present invention preferably has a minimum fiber diameter of more than 100 nm, more preferably more than 150 nm, and even more preferably more than 200 nm.The long fine aramid single fiber of the present invention preferably has a minimum fiber diameter of 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less.

[0031] The long fine aramid single fiber of the present invention has an average fiber diameter of preferably less than 1000 nm, more preferably less than 950 nm, and even more preferably less than 900 nm. The long fine aramid single fiber of the present invention has an average fiber diameter of preferably more than 400 nm, more preferably more than 500 nm, and even more preferably more than 600 nm. The average fiber diameter of the long fine aramid single fiber of the present invention is preferably more than 400 nm and less than 1000 nm, more preferably more than 500 nm and less than 950 nm, and even more preferably more than 600 nm and less than 900 nm.

[0032] The maximum fiber diameter, minimum fiber diameter and average fiber diameter of the long fine aramid single fibers of the present invention can be determined in a set of a predetermined number of fibers. Specifically, the fiber diameters of 100 long fine aramid single fibers of the present invention are measured by observation with an electron microscope such as SEM, the maximum fiber diameter is the maximum fiber diameter, the minimum fiber diameter is the minimum fiber diameter, and the number average value of the fiber diameters can be the average fiber diameter.

[0033] The long fine aramid single fiber of the present invention is a relatively long fiber having a minimum fiber length of more than 10 μm. The minimum fiber length of the long fine aramid single fiber of the present invention is preferably more than 20 μm, more preferably more than 30 μm, more preferably more than 40 μm, more preferably more than 50 μm, and even more preferably more than 60 μm. On the other hand, the upper limit of the minimum fiber length of the long fine aramid single fiber of the present invention is not particularly limited, but can be, for example, less than 100 μm.

[0034] The maximum fiber length of the long fine aramid single fibers of the present invention is preferably less than 1000 μm, more preferably less than 800 μm, and even more preferably less than 600 μm.The maximum fiber length of the long fine aramid single fibers of the present invention is preferably 200 μm or more, more preferably 250 μm or more, and even more preferably 300 μm or more.

[0035] The average fiber length of the long fine aramid single fiber of the present invention is preferably more than 20 μm, more preferably more than 50 μm, and even more preferably more than 80 μm. The average fiber length of the long fine aramid single fiber of the present invention is preferably less than 400 μm, more preferably less than 300 μm, and even more preferably less than 200 μm. The average fiber length of the long fine aramid single fiber of the present invention is preferably more than 20 μm and less than 400 μm, preferably more than 50 μm and less than 300 μm, and even more preferably more than 80 μm and less than 200 μm.

[0036] The minimum fiber length, maximum fiber length and average fiber length of the long fine aramid single fibers of the present invention can be determined for a set of a predetermined number of fibers. Specifically, the fiber lengths of 100 long fine aramid single fibers of the present invention are measured by observation with an electron microscope such as SEM, and the minimum fiber length and the maximum fiber length are taken as the minimum fiber length and the maximum fiber length, respectively, and the number average value of the fiber lengths can be taken as the average fiber length.

[0037] The long fine aramid single fiber of the present invention is a fiber having a relatively high aspect ratio. The minimum aspect ratio of the long fine aramid single fiber of the present invention is preferably 80 or more, more preferably 90 or more, and more preferably 100 or more. On the other hand, the maximum aspect ratio of the long fine aramid single fiber of the present invention is not particularly limited, but can be, for example, less than 500. The average aspect ratio of the long fine aramid single fiber of the present invention is preferably 100 or more, more preferably 150 or more, and even more preferably 200 or more. The upper limit of the average aspect ratio of the long fine aramid single fiber of the present invention is not particularly limited, but can be, for example, less than 400.

[0038] The minimum aspect ratio, maximum aspect ratio and average aspect ratio of the long fine aramid single fiber of the present invention can also be determined for a set of a predetermined number of fibers. Specifically, the fiber lengths of 100 long fine aramid single fibers of the present invention are measured by observation with an electron microscope such as SEM, and the aspect ratio of each fiber is determined from the fiber length and fiber diameter of each fiber. Among them, the minimum aspect ratio and the maximum aspect ratio are taken as the minimum aspect ratio and the maximum aspect ratio, respectively, and the number average value thereof can be taken as the average aspect ratio.

[0039] The long and fine aramid single fiber of the present invention has a relatively high crystallinity. x = (1-ΔQx / ΔQ0) × 100 (%) (In the ceremony ΔQx is the change in heat capacity before and after the glass transition point of the long fine aramid single fiber of the present invention, The crystallinity x determined by ΔQ0 is the amount of change in heat capacity before and after the glass transition point of amorphous aramid) is 60% or more. The crystallinity of the long fine aramid single fiber of the present invention is preferably 70% or more, and more preferably 80% or more. There is no particular upper limit to the crystallinity of the long fine aramid single fiber of the present invention, but it can be, for example, 95% or less or 90% or less.

[0040] As the amorphous aramid, an aramid that is completely soluble in dimethyl sulfoxide (in the absence of a base) at room temperature (25° C.) can be used.

[0041] ΔQx and ΔQ0 in the above formula can be determined by a differential scanning calorimeter. Specifically, the variation in specific heat capacity versus temperature is plotted on a plane with the vertical axis being the specific heat capacity and the horizontal axis being the temperature using a differential scanning calorimeter to determine a temperature-dependent specific heat capacity baseline. The glass transition point is then identified based on the shift location of the baseline, and the amount of change in heat capacity can be determined from the baseline shift interval before and after the glass transition point. The baseline shift interval can be determined by linearly approximating the baseline.

[0042] The measurement or determination of the crystallinity of a polymer by the above formula is known, as described, for example, in Polymer Journal, Vol. 31, No. 2, pp. 138-139 (1972).

[0043] The long fine aramid single fibers of the present invention preferably have a glass transition point of more than 300° C., more preferably more than 310° C., and even more preferably more than 320° C. A high glass transition point means that there are few amorphous parts that undergo Brownian motion and that the crystallinity is high.

[0044] The long fine aramid single fiber of the present invention is a single fiber and is unbranched, and therefore has excellent mixability with resins and the like.

[0045] In addition, the long fine aramid single fibers of the present invention are fine but relatively long, and therefore can exhibit superior mechanical properties when combined with a resin or the like.

[0046] Furthermore, the long and fine aramid single fibers of the present invention have high crystallinity, and therefore the fiber shape is stable and can be well maintained against various physical or chemical actions.

[0047] [Manufacturing method of long fine aramid single fibers] The method for producing the long fine aramid single fibers of the present invention comprises the steps of: A swelling step of bringing raw material aramid fibers having a soluble content in dimethyl sulfoxide of 10% by mass or more into contact with a swelling liquid containing an aprotic solvent to cause the fibers to swell; A mechanical defibration step of finely pulverizing the raw aramid fibers by mechanical defibration; and A separation step of separating long fine aramid single fibers having a fiber diameter of less than 2000 nm and a fiber length of more than 10 μm from the finely divided raw aramid fibers. Includes.

[0048] The method for producing long and fine aramid single fibers of the present invention is characterized in that, instead of spinning an aramid solution, a predetermined raw material aramid fiber is swelled and mechanically opened up to form single fibers.

[0049] The method for producing long and fine aramid single fibers of the present invention can produce aramid fibers which are very fine, long and have a high degree of crystallinity.

[0050] When an aramid solution is spun, it is difficult to produce a relatively long aramid fiber, but the method for producing long and fine aramid single fibers of the present invention can easily produce a relatively long aramid single fiber.

[0051] The method for producing long and fine aramid single fibers of the present invention can exhibit high productivity and is industrially advantageous. On the other hand, although it is known to produce aramid single fibers by electrospinning, the productivity of electrospinning is low and it is disadvantageous for industrial production.

[0052] The method for producing the long and fine aramid single fibers of the present invention will be described below in detail.

[0053] (raw materials) In the method for producing long and fine aramid single fibers of the present invention, aramid fibers having a dimethyl sulfoxide soluble content of 10% by mass (weight) or more are used as a raw material. The soluble content of the raw material aramid fibers is based on the total mass (total weight) of the raw material aramid fibers.

[0054] As the raw aramid fiber having a soluble content in dimethyl sulfoxide of 10 mass (weight) % or more, aramid fiber that shows a mass (weight) change of 10% or more when immersed in dimethyl sulfoxide (having a purity of 99.5% or more and not containing bases such as sodium hydroxide and potassium hydroxide) at room temperature (25°C) for 72 hours can be used.

[0055] In raw aramid fibers having a dimethyl sulfoxide soluble content of 10% by mass (weight) or more, the amorphous portion is easily solvated, and the fibers are easily swollen. The dimethyl sulfoxide soluble content of the raw aramid fibers is not particularly limited as long as it is 10% by mass (weight) or more, but may be, for example, 15% by mass (weight) or more, 20% by mass (weight) or more, 25% by mass (weight) or more, or 30% by mass (weight) or more. On the other hand, the dimethyl sulfoxide soluble content of the raw aramid fibers is preferably 80% by mass (weight) or less, more preferably 70% by mass (weight) or less, and even more preferably 60% by mass (weight) or less.

[0056] The form of the raw aramid fiber is not particularly limited, and either branched or unbranched fibers can be used. For example, the raw aramid fiber may be in the form of aramid floc or aramid fibrids.

[0057] "Aramid floc" refers to short fibers made of aramid. The (number) average fiber length of the aramid floc is not particularly limited, but can be, for example, in the range of 1 to 50 mm, preferably in the range of 2 to 40 mm, and more preferably in the range of 3 to 30 mm. The (number) average fiber diameter of the aramid floc is also not particularly limited, but can be, for example, in the range of 10 to 30 μm, preferably in the range of 12 to 28 μm, and more preferably in the range of 14 to 26 μm.

[0058] The average fiber length and average fiber diameter of the aramid flocs can be obtained by averaging the lengths and widths of a predetermined number of aramid flocs (for example, 100 flocs). Specifically, the fiber lengths and fiber diameters of 100 flocs of the aramid flocs can be measured by observation with an electron microscope such as SEM, and the average value of the fiber lengths can be taken as the average fiber length and the average value of the fiber diameters can be taken as the average fiber diameter.

[0059] "Aramid fibrids" are film-like or fibrous fine particles made of aramid, and are sometimes called aramid pulp (for details on aramid fibrids, see JP-B-35-11851 and JP-B-37-5752, etc.). Since fibrids have papermaking properties similar to ordinary wood (cellulose) pulp, they can be formed into a sheet using a papermaking machine after being dispersed in water.

[0060] The (number) average fiber diameter of the aramid fibrids is not particularly limited, but can be, for example, 4 to 40 μm, preferably in the range of 5 to 35 μm, and more preferably 6 to 30 μm.

[0061] The average fiber diameter of the aramid fibrids can be obtained by averaging the widths of a predetermined number of aramid fibrids (for example, 100 fibers). Specifically, the fiber diameters of 100 fibers of the aramid fibrids can be measured by observation with an electron microscope such as SEM, and the average value of the fiber diameters can be used as the average fiber diameter.

[0062] (Swelling process) In the swelling step of the method for producing long and fine aramid single fibers of the present invention, raw material aramid fibers having a soluble content in dimethyl sulfoxide of 10 mass (weight) % or more are brought into contact with a swelling liquid containing an aprotic solvent to cause swelling.

[0063] The aprotic solvent is not particularly limited as long as it can swell the raw material aramid fibers, but dimethyl sulfoxide, dimethyl acetamide, or a mixture of the two can be preferably used.

[0064] It is believed that the aprotic solvent breaks hydrogen bonds between low crystallinity portions of the raw aramid fibers, and the highly crystalline portions other than the broken portions are easily separated as fine fibers.

[0065] The swelling liquid may contain optional components other than the aprotic solvent, such as an acid, a base, a salt, water, etc. The amount of the optional components is not particularly limited, but may be, for example, 0.001 to 10% by mass (weight), 0.01 to 5% by mass (weight), or 0.1 to 1% by mass (weight) based on the total mass (total weight) of the swelling liquid.

[0066] The mode of contacting the raw aramid fibers with the swelling liquid is not particularly limited, and for example, the raw aramid fibers can be immersed in the swelling liquid or the swelling liquid can be sprinkled or sprayed onto the raw aramid fibers. The mode of immersing the raw aramid fibers in the swelling liquid is preferred.

[0067] The contact temperature and contact time are not particularly limited as long as the raw material aramid fibers swell, and may be, for example, in the range of room temperature (25° C.) to 40° C. and 10 minutes to 1 hour.

[0068] The raw aramid fibers swollen in the swelling step are subjected to a mechanical defibration step.

[0069] (Mechanical defibration process) In the mechanical fiber-opening step of the method for producing long and fine aramid single fibers of the present invention, the raw material aramid fibers after the swelling step are finely divided by mechanical fiber-opening.

[0070] It is considered that, through the swelling step, hydrogen bonds between the low crystalline portions in the raw aramid fibers are cut, and the portions become easily separated, and then, due to mechanical defibration, a physical force such as a shear force acts on the portions, causing the fine fibers to be separated from the raw aramid fibers.

[0071] The mechanical defibration can be carried out by a known method as long as the defibration is mechanical. The mechanical defibration is preferably carried out by applying a shear force to the swollen raw material aramid fibers.

[0072] The device used for mechanical fiberization is not particularly limited, and examples that can be used include devices that apply collision shear force such as planetary ball mills and bead mills, devices that apply rotational shear force such as disk refiners and grinders, devices capable of performing kneading, stirring and dispersion with high efficiency such as various kneaders and planetary mixers, high-pressure homogenizers, etc. It is preferable to use a Clearmix device (for example, one manufactured by MTECHNIQUE) equipped with a high-speed rotating rotor and a screen arranged with a small clearance.

[0073] (separation process) In the separation step of the method for producing long fine aramid single fibers of the present invention, long fine aramid single fibers having a fiber diameter of less than 2000 nm and a fiber length of more than 10 μm are separated from the fine raw material aramid fibers after the mechanical fiberization step.

[0074] In the separation step, long fine aramid single fibers having a fiber diameter of less than 2000 nm and a fiber length of more than 10 μm are separated from the fine fibers separated from the raw aramid fibers in the mechanical defibration step.

[0075] The separation method is not particularly limited, and can be performed by a known method. For example, the raw aramid fibers finely divided in the mechanical fiberization step can be diluted and then centrifuged, and the supernatant can be filtered to separate the long fine aramid single fibers having a fiber diameter of less than 2000 nm and a fiber length of more than 10 μm from the raw aramid fibers.

[0076] The dilution medium (liquid) is preferably an aprotic solvent. As the aprotic solvent, dimethylsulfoxide, dimethylacetamide, or a mixture of the two can be preferably used. The dilution medium may contain optional components other than the aprotic solvent, such as acids, bases, salts, and water, as necessary. The amount of the optional components is not particularly limited, but may be, for example, 0.001 to 10% by mass (weight), 0.01 to 5% by mass (weight), or 0.1 to 1% by mass (weight) based on the total mass (total weight) of the dilution medium (liquid).

[0077] The long and fine aramid single fibers of the present invention can be obtained by the method for producing the long and fine aramid single fibers of the present invention.

[0078] In particular, the method for producing long and fine aramid single fibers of the present invention can produce long and fine aramid single fibers of the present invention having a glass transition point 30° C. or more higher than that of the raw aramid fibers. A high glass transition point means that there are fewer amorphous parts that undergo Brownian motion and that the crystallinity is high. Therefore, the method for producing long and fine aramid single fibers of the present invention can produce long and fine aramid single fibers having a higher degree of crystallinity than the raw aramid fibers.

[0079] [Composite material or sheet containing long fine aramid single fibers] The present invention also relates to a composite material or sheet containing the above-mentioned long fine aramid monofilaments.

[0080] (composite material) The composite material of the present invention contains the above-mentioned long fine aramid monofilaments and a matrix resin.

[0081] It is preferable that the long fine aramid single fibers are dispersed in the matrix resin. The long fine aramid single fibers are not branched, so that they can be easily mixed with the matrix resin. In addition, the long fine aramid single fibers are relatively long, so that the mechanical strength of the composite material can be easily increased.

[0082] The matrix resin is not particularly limited, and a thermoplastic resin, a thermosetting resin, or a mixture of both can be used.

[0083] The type of thermoplastic resin is not particularly limited, and one or more of polyolefin resin, nylon resin, polycarbonate resin, polyester resin, polyacetal resin, ABS resin, phenoxy resin, polymethyl methacrylate resin, polyphenylene sulfide resin, polyetherimide resin, polyether ketone resin, etc. can be used.

[0084] The type of thermosetting resin is not particularly limited, and one or more of epoxy resins, unsaturated polyester resins, vinyl ester resins, etc. can be used. Epoxy resins are preferred.

[0085] The mass (weight) ratio of the matrix resin to the above-mentioned long fine aramid single fibers (mass (weight) of matrix resin / mass (weight) of long fine aramid single fibers) is preferably 50 / 50 to 90 / 10, more preferably 55 / 45 to 80 / 20, and particularly preferably 60 / 40 to 70 / 30, from the viewpoint of strength of the composite material.

[0086] When the matrix resin is a thermoplastic resin, the composite material of the present invention can be obtained, for example, by introducing the long fine aramid single fibers into a molten thermoplastic matrix resin, mixing and kneading the mixture, and subjecting the mixture to extrusion molding or injection molding.

[0087] When the matrix resin is a thermosetting resin, the composite material of the present invention can be obtained, for example, by mixing the long fine aramid single fibers with the matrix resin and molding the mixture under heat. The composite material does not need to be completely cured, but it is preferable that the molded composite material is cured to such an extent that the molded composite material can maintain its shape. After molding, the material may be further heated to be completely cured.

[0088] The composite material of the present invention can have a higher dielectric strength than the matrix resin itself, and therefore can be suitably used as an electrical insulator.

[0089] In particular, the composite material of the present invention can have a higher glass transition point than the matrix resin itself, and therefore has a more stable shape than the matrix resin, making it suitable for use in a variety of applications.

[0090] (Sheet) The sheet of the present invention contains the above-mentioned long fine aramid monofilaments.

[0091] The sheet of the present invention containing the above-mentioned long fine aramid monofilaments can exhibit excellent strength, electrical insulation properties, and the like.

[0092] The sheet of the present invention is preferably porous. The form of the sheet of the present invention is not particularly limited, and various forms such as woven fabric, nonwoven fabric, paper, etc. are included, but the form of nonwoven fabric or paper is preferable.

[0093] The thickness of the sheet of the present invention is preferably from 1 to 300 μm, more preferably from 2 to 200 μm, and even more preferably from 3 to 100 μm. The basis weight of the sheet of the present invention is from 10 to 500 g / m2 is preferable, and 20 to 400 g / m 2 More preferably, 30 to 300 g / m 2 is even more preferred.

[0094] The sheet of the present invention contains the above-mentioned long and fine aramid single fibers in an amount of preferably 50 to 99% by mass (weight), more preferably 60 to 95% by mass (weight), and even more preferably 70 to 90% by mass (weight) of the total mass (total weight) of the sheet.

[0095] The sheet of the present invention is preferably mainly composed of the long fine aramid fibers (80% by mass (weight) or more of the total mass). When the sheet of the present invention mainly contains the long fine aramid single fibers, it is easy to reduce the thickness of the sheet and obtain a very thin sheet.

[0096] The sheet of the present invention can be produced, for example, by forming the long fine aramid single fibers into a sheet by a known method. Specifically, for example, a method of dispersing the long fine aramid single fibers, if necessary, together with other fibers, etc., in a dry state to form a sheet; a method of dispersing and mixing the long fine aramid single fibers, if necessary, together with other fibers, etc., in a liquid medium such as water to obtain a slurry, discharging the slurry onto a liquid-permeable support such as a net or belt to form a sheet, and then removing the liquid medium and drying can be used, but the latter method is preferred, and among these, a so-called wet papermaking method using water as the liquid medium is preferred.

[0097] In the wet papermaking method, an aqueous slurry containing at least the long fine aramid single fibers is generally fed to a papermaking machine, dispersed therein, dehydrated, squeezed out water, and dried to wind up a sheet (wet papermaking method). As the papermaking machine, a Fourdrinier papermaking machine, a cylinder papermaking machine, an inclined papermaking machine, or a combination papermaking machine combining these machines can be used. During papermaking, additives such as a dispersibility improver, an antifoaming agent, and a paper strength enhancer are used as necessary. EXAMPLES

[0098] The present invention will be described in more detail below using examples and comparative examples, but the scope of the present invention is not limited to the examples. Each example and comparative example was evaluated by the following methods.

[0099] <Measurement of soluble matter> 0.1 g of raw aramid fiber, long fine aramid single fiber, or amorphous aramid nanofiber was put into 10 g of dimethyl sulfoxide and immersed at room temperature (25°C) for 72 hours. When the measurement target was fiber, it was suction filtered with a membrane filter (Merck Millipore, hydrophilic PTFE, hole size: 1.0 um (raw aramid fiber), 0.2 um (long fine aramid single fiber and amorphous aramid nanofiber)), washed thoroughly with 99.0 mass% dimethyl sulfoxide, and then washed with deionized water. The washed filter cake was dried at 105°C for 24 hours, and the mass was used as the insoluble content to calculate the soluble content using the following formula. Soluble content (%) = (1-insoluble content / 0.1)*100%

[0100] <Measurement of glass transition temperature> Long fine aramid single fibers or amorphous aramid nanofibers were washed with deionized water and dried in an oven at 105°C for 24 hours, and the change in heat capacity was measured under the following conditions, and the midpoint of the baseline change was taken as the glass transition point. Differential scanning calorimetry: Netsch Japan Co., Ltd. DSC214-SKK27 Temperature range: Heating process 25~340℃ 10℃ / min Atmosphere: Nitrogen gas 40ml / min Sample container: Aluminum standard container (with lid)

[0101] <Measurement of crystallinity> The long fine aramid single fibers and amorphous aramid nanofibers were washed with dimethyl sulfoxide and deionized water in that order, and then dried in an oven at 105°C for 24 hours. After that, the change in heat capacity of each was measured under the following conditions. Differential scanning calorimeter: Hitachi High-Tech Science Corporation, Model X-DSC7000. Temperature range: Heating process 25~340℃ 10℃ / min Cooling process 340~25℃ 20℃ / min Atmosphere: Nitrogen gas 40ml / min Sample container: Aluminum standard container (with lid) Standard material: Sapphire The crystallinity of the long fine aramid single fiber was determined by the following formula. x = (1-ΔQx / ΔQ0) × 100 (%) ΔQx: Change in heat capacity of long fine aramid single fiber around the glass transition point ΔQ0: Heat capacity change before and after the glass transition point of amorphous aramid nanofiber

[0102] <Measurement of fiber diameter and length> The long fine aramid single fibers or amorphous aramid nanofibers were washed with deionized water and dried in an oven at 105°C, and then measured under the following conditions, and the maximum fiber diameter, minimum fiber diameter, maximum fiber length and minimum fiber length were determined by image analysis. Microscope: Field emission scanning electron microscope: Hitachi High-Tech Corporation SU8010 Voltage: 5kV Number of measurements: 100

[0103] <Measurement of glass transition temperature of composite materials> A composite material containing long fine aramid single fibers or amorphous aramid nanofibers and a matrix resin was dried at 80°C and reduced pressure of -100 kPa, and then the change in heat capacity of the composite material was measured under the following conditions, and the midpoint of the baseline change was determined as the glass transition point. Differential scanning calorimetry: Netsch Japan Co., Ltd. DSC214-SKK277 Temperature range: Heating process 25~140℃ 10℃ / min Atmosphere: Nitrogen gas 40ml / min Sample container: Aluminum standard container (with lid)

[0104] <Measurement of dielectric strength of composite materials> A composite material containing long fine aramid single fibers or amorphous aramid nanofibers and a matrix resin was molded into a 6 cm x 6 cm film, washed with deionized water, dried at 80°C and -100 kPa under reduced pressure, and measured under the following conditions. High voltage withstand voltage tester: Measurement Technology Laboratory Co., Ltd. Voltage Tester 7473 Rmap Up: 30 seconds Voltage range: 0~20kV Under the above conditions, the dielectric strength was calculated from the breakdown voltage of the composite material and the film thickness using the following formula. Dielectric strength (kV / mm) = Breakdown voltage (kV) / Film thickness (mm)

[0105] <Measurement of soluble content in composite materials> 0.1 g of a composite material containing long fine aramid single fibers or amorphous aramid nanofibers and a matrix resin was added to 10 g of dimethyl sulfoxide and immersed at room temperature (25°C) for 72 hours. This was suction filtered with a membrane filter (Merck Millipore, hydrophilic PTFE, pore size: 2.0 um), washed thoroughly with 99.0 mass% dimethyl sulfoxide, and then washed with deionized water. The washed filter cake was dried at 80°C for 24 hours, and the mass was used as the insoluble matter to calculate the soluble matter using the following formula. Soluble content (%) = (1-insoluble content / 0.1)*100%

[0106] <Example 1: Preparation of long and fine aramid single fibers> 2 g of raw aramid fiber was dried in an oven at 105°C for 24 hours, then added to 198 g of dimethyl sulfoxide to swell it, and mixed at 10,000 rpm for 60 minutes in a homomixer (Primix Corporation, MARKII2.5 type). This was then mixed at 10,000 rpm for 20 minutes in a clear mixer (M Technique Corporation, CLM0.8) to obtain a dispersion of long and fine aramid single fibers. The obtained long fine aramid single fiber dispersion was suction filtered through a membrane filter having a pore size of 0.2 μm and dried in an oven at 105° C., and the maximum fiber diameter, minimum fiber diameter, maximum fiber length, minimum fiber length, soluble content, crystallinity, and glass transition point of the long fine aramid single fibers were measured (see FIGS. 1 to 3 and Table 1). On the other hand, the obtained dispersion of long and fine aramid single fibers was centrifuged at 16,000 G, the dimethyl sulfoxide was removed by decantation, and the precipitate was collected. The above precipitate was mixed with N,N'-dimethylacetamide, centrifuged again at 16,000 G, and decanted to recover the precipitate. This procedure was repeated three times to obtain a paste of long and fine aramid single fibers. The solid content of the resulting paste was 10% by mass. Raw material aramid fiber: TAK.inc. m-Aramid Floc, soluble content 20% by mass Dimethyl sulfoxide Fujifilm Wako Pure Chemical Industries, Ltd. Special grade 99.0% by mass Dimethylacetamide Fujifilm Wako Pure Chemical Industries, Ltd. Special grade 99.0% by mass

[0107] <Example 2: Preparation of a composite material containing 10% by mass of long fine aramid single fibers> As a solvent, 10 g of dimethylacetamide and 10 g of acetone were mixed, and 51.09 g of the base material EPICLON850, 28.27 g of the hardener TD-2131, and 0.794 g of the hardener 2P4MHZ-pw were added and stirred until the appearance became uniform, and further, 80.1 g of the paste containing the long fine aramid single fibers produced in Example 1 was added. The resulting composition was stirred and degassed using a shear mixer (SK-300SII, manufactured by KAKUHUNTER) and cast onto a PET film. The cast PET film was heated on a hot plate at 100° C. for 1 hour, and the pre-cured composition was peeled off from the film and cured in an oven at 170° C. for 2 hours. The resulting composite material was washed with deionized water, dried, and subjected to insulation resistance measurements (see Table 2). Bisphenol A epoxy resin DIC Corporation EPICLON850 Phenolite resin DIC Corporation TD-2131 2-Phenyl-4-methylimidazole Shikoku Chemical Industry Co., Ltd. 2P4MHZ-pw Acetone Fujifilm Wako Pure Chemicals, purity 99.5% by mass Dimethylacetamide Fujifilm Wako Pure Chemical Industries, Ltd. Special grade 99.0% by mass

[0108] <Example 3: Preparation of a composite material containing 30% by mass of long fine aramid single fibers> As a solvent, 10 g of dimethylacetamide and 10 g of acetone were mixed, and 51.09 g of the base material EPICLON850, 28.27 g of the hardener TD-2131, and 0.794 g of the hardener 2P4MHZ-pw were added and stirred until the appearance became uniform, and 240.3 g of the paste containing the long fine aramid single fibers produced in Example 1 was further added. The resulting composition was stirred and degassed using a shear mixer (SK-300SII, manufactured by KAKUHUNTER) and cast onto a PET film. The cast PET film was heated on a hot plate at 100° C. for 1 hour, and the pre-cured composition was peeled off from the film and cured in an oven at 170° C. for 2 hours. The resulting composite material was washed with deionized water, dried, and the soluble content and glass transition temperature were measured (see Table 2). Bisphenol A epoxy resin DIC Corporation EPICLON850 Phenolite resin DIC Corporation TD-2131 2-Phenyl-4-methylimidazole Shikoku Chemical Industry Co., Ltd. 2P4MHZ-pw Acetone Fujifilm Wako Pure Chemicals, purity 99.5% by mass Dimethylacetamide Fujifilm Wako Pure Chemical Industries, Ltd. Special grade 99.0% by mass

[0109] <Comparative Example 1: Preparation of amorphous aramid nanofibers> 3 g of potassium hydroxide and 4 g of water were stirred, and then added to 2 g of raw aramid fiber that had been dried in an oven at 105°C for 24 hours and 198 g of dimethyl sulfoxide, heated at 70°C, stirred for 60 minutes, and further mixed with 100 g of dimethyl sulfoxide to prepare an aramid fiber dispersion. The obtained aramid fiber dispersion was poured into a vessel containing 2 L of deionized water while stirring. The above deionized water was neutralized with sulfuric acid until the pH reached 7±0.1 on a pH meter (LAQUAtwin, manufactured by Horiba, Ltd.), centrifuged at 16,000G, the supernatant was removed by decantation, 200g of deionized water was added, and the mixture was centrifuged again at 16,000G. The supernatant was removed by decantation, and 200 g of deionized water was added to obtain an amorphous aramid nanofiber dispersion. The obtained amorphous aramid nanofiber dispersion was dried, and the maximum fiber diameter, minimum fiber diameter, maximum fiber length, minimum fiber length, soluble content, and glass transition point were measured. Since the soluble content of the amorphous aramid nanofiber was 100%, the crystallinity of the amorphous aramid nanofiber was set to 0 (see Table 1). Meanwhile, 220 g of the obtained amorphous aramid nanofiber dispersion was dried in an oven at 105°C, and 198 g of dimethylacetamide was added and mixed until uniformly dispersed. The mixture was centrifuged at 16,000 G and decanted to obtain a paste of amorphous aramid nanofiber. The solid content of the resulting paste was 10% by mass. Raw material aramid fiber: TAK.inc. m-Aramid Floc, soluble content 20% by mass Dimethyl sulfoxide Fujifilm Wako Pure Chemical Industries, Ltd. Special grade 99.0% by mass Dimethylacetamide Fujifilm Wako Pure Chemical Industries, Ltd. Special grade 99.0% by mass Potassium hydroxide Fujifilm Wako Pure Chemical Industries, Ltd. Special grade Purity 85.0% by mass Sulfuric acid Fujifilm Wako Pure Chemical Industries, Ltd. Special grade Purity 95.0% by mass

[0110] <Comparative Example 2: Preparation of a composite material containing 10% by mass of amorphous aramid nanofiber> A composite material was produced in the same manner as in Example 2, except that the paste of amorphous aramid nanofiber obtained in Comparative Example 1 was used.

[0111] <Comparative Example 3: Preparation of a composite material containing 30% by mass of amorphous aramid nanofiber> A composite material was produced in the same manner as in Example 3, except that the paste of amorphous aramid nanofiber obtained in Comparative Example 1 was used.

[0112] The maximum fiber diameter, minimum fiber diameter, maximum fiber length, minimum fiber length, soluble content, crystallinity and glass transition point (Tg) of the long fine aramid single fiber of Example 1 and the amorphous aramid nanofiber of Comparative Example 1 are shown in Table 1 below.

[0113] [Table 1]

[0114] The dielectric strength of the composite materials of Example 2 and Comparative Example 2, and the glass transition point and soluble content of the composite materials of Example 3 and Comparative Example 3 are shown in Table 2 below.

[0115] [Table 2]

[0116] The long fine aramid single fiber obtained in Example 1 had a maximum fiber diameter of 1960 nm, a minimum fiber diameter of 300 nm, a maximum fiber length of 360 um, a minimum fiber length of 70 μm, and a degree of crystallinity of 80%, and it was confirmed by SEM observation that it was a single fiber without branching (FIGS. 1 to 3). On the other hand, the amorphous aramid nanofiber obtained in Comparative Example 1 had a maximum fiber diameter of 200 nm, a minimum fiber diameter of 10 nm, a maximum fiber length of 10 μm, and a minimum fiber length of 0.1 um. In addition, the insulation resistance (dielectric strength) of Examples 2 and 3, which are composite materials containing long fine aramid single fibers and a matrix resin, was as high as 27.5 kV / mm, the glass transition point rose to 130° C. or higher, and the soluble content was 0 mass%. On the other hand, the insulation resistance (dielectric strength) of Comparative Examples 2 and 3, which are composite materials containing amorphous aramid nanofibers and a matrix resin, was low at 6.0 kV / mm, the glass transition point was almost unchanged from the raw material epoxy resin (glass transition point: 93°C), and the soluble content was 12 mass%.

Claims

1. The maximum fiber diameter is less than 2000 nm; A long fine aramid single fiber having a minimum fiber length of more than 10 μm, The following formula x=(1-ΔQ x / ΔQ 0 )×100(%) (In the ceremony ΔQ x is the change in heat capacity of the long fine aramid single fiber before and after the glass transition point, ΔQ 0 The crystallinity x determined by the above-mentioned method (wherein x is the amount of change in heat capacity before and after the glass transition point of amorphous aramid) is 60% or more.

2. 2. The long fine aramid single fiber according to claim 1, having an average fiber diameter of less than 1000 nm.

3. 2. The long and fine aramid single fiber according to claim 1, having an average aspect ratio of 100 or more.

4. 2. The long fine aramid single fiber according to claim 1, having a glass transition point of more than 300°C.

5. 2. The long fine aramid filament of claim 1, wherein said aramid is a meta-aramid.

6. A swelling step of bringing raw material aramid fibers having a soluble content in dimethyl sulfoxide of 10% by mass or more into contact with a swelling liquid containing an aprotic solvent to cause the fibers to swell; A mechanical defibration step of finely pulverizing the raw aramid fibers by mechanical defibration; and A separation step of separating long fine aramid single fibers having a fiber diameter of less than 2000 nm and a fiber length of more than 10 μm from the finely divided raw aramid fibers. The method for producing the long fine aramid single fiber according to claim 1, comprising:

7. The process according to claim 6, wherein the aprotic solvent is dimethylsulfoxide and / or dimethylacetamide.

8. 7. The method according to claim 6, wherein the glass transition point of the long fine aramid single fibers is higher by 30° C. or more than the glass transition point of the raw material aramid fibers.

9. A composite material comprising the long fine aramid monofilament according to claim 1 and a matrix resin.

10. 10. The composite material according to claim 9, wherein the long fine aramid monofilaments are dispersed in the matrix resin.

11. The composite material of claim 9 , wherein the matrix resin is an epoxy resin.

12. A sheet comprising the long fine aramid monofilaments according to claim 1.

Citation Information

Patent Citations

  • Separator and manufacturing method thereof

    JP2023002089A